Pelatihan Inovasi Minuman Kopi dan Strategi Pemasaran Digital di Kampung Wisata Kopi Sangit Bawah Langit - Hetty Yulianti Sihite; Fitriana Baitanu; Welli Braham Kurniawan; Rafael Dolyardo; M. Al Amin Agma (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Kampung Wisata Kopi Sangit Bawah Langit (KSBL) in Bintan Regency is a community-based tourism village with strong potential through its distinctive local “kopi sangit” product. However, the development of this potential still faces several challenges, particularly limited product innovation, packaging design, and low community digital literacy in online marketing. This community service program aimed to improve community capacity in developing coffee-based beverage innovations and implementing social media-based digital marketing strategies. The program applied participatory and experiential learning approaches through observation, Focus Group Discussions (FGD), training sessions, demonstrations, hands-on practice, and evaluation using pre-test and post-test methods. The activity was conducted on 14–15 September 2025 and involved 15 participants consisting of PKK women members and tourism village managers. The results indicated a 65% increase in participants’ understanding, especially in product innovation and digital marketing aspects. The program also produced innovative coffee-based products such as lemongrass coffee mocktails, pandan iced coffee, and herbal coffee syrup. In addition to improving technical skills, the activity strengthened participants’ creativity, entrepreneurial motivation, and community collaboration in supporting the development of the creative economy and community-based tourism in Bintan Regency.